Beyond Ease of Use: How Consumer Innovativeness Shapes University Students’ Purchase Intention Toward Health-Oriented Wearable Devices Through Usefulness and Enjoyment - Tian Xinyu; Deok-Jin Jang; Dong-Kyu Kim; Chulhwan Choi (Social Sciences, 2026)
This study examines how consumer innovativeness shapes university students’ purchase intention toward health-oriented wearable devices and how perceived ease of use, usefulness, and enjoyment transmit that influence. A survey was administered to undergraduates at universities in China using convenience sampling (N = 435). Confirmatory factor analysis, structural equation modelling, and bias-corrected bootstrapping were performed. Consumer innovativeness positively affected perceived ease of use, usefulness, and enjoyment. Perceived ease of use positively influenced perceived usefulness, which in turn enhanced perceived enjoyment. Perceived usefulness and enjoyment significantly increased purchase intention, whereas perceived ease of use had no direct effect. Effect decomposition showed, however, that perceived ease of use exerted a significant total effect (β = 0.276) operating entirely through usefulness and enjoyment, and that the sequential pathway from ease of use through usefulness and enjoyment to purchase intention was significant. Purchase intention toward health-oriented wearable devices is therefore formed through a multilayered mechanism in which cognitive evaluation precedes affective experience. A non-significant direct path should not be read as evidence that ease of use has ceased to matter.